2022
DOI: 10.1088/1742-6596/2265/4/042017
|View full text |Cite
|
Sign up to set email alerts
|

An engineering modification to the blade element momentum method for floating wind turbines

Abstract: The design of next-generation offshore wind rotors for floating applications carries large uncertainties that make it harder to bring costs down. A significant share of this uncertainty is associated with the use of Blade Element Momentum (BEM) methods to run aeroelastic design and loadcase calculations, because the assumptions underlying the momentum theory are violated by the floater motion. This work presents an engineering method for BEM that allows to model generic floater motions and improves the aerodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The FVW simulations also showed a slight dependency of the mean power on the wave-induced motions, which was not the case in the BEMT simulations. In addition, simulations by Mancini et al [16] showed that the amplitude of power and thrust of a model rotor undergoing an exemplary periodic surge motion calculated by a BEMT method is smaller in comparison to the lifting-line FVW method AWSM [17]. Based on this observation, Mancini et al presented a new correction model for BEMT methods, which showed better agreement in the presented case.…”
Section: Previous Work On Wind Turbine Rotors In Surge Motionmentioning
confidence: 85%
“…The FVW simulations also showed a slight dependency of the mean power on the wave-induced motions, which was not the case in the BEMT simulations. In addition, simulations by Mancini et al [16] showed that the amplitude of power and thrust of a model rotor undergoing an exemplary periodic surge motion calculated by a BEMT method is smaller in comparison to the lifting-line FVW method AWSM [17]. Based on this observation, Mancini et al presented a new correction model for BEMT methods, which showed better agreement in the presented case.…”
Section: Previous Work On Wind Turbine Rotors In Surge Motionmentioning
confidence: 85%